2020
DOI: 10.1002/pi.6112
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the production and molecular weight of levan in enzymatic synthesis by recombinant Bacillus subtilis levansucrase SacB‐T305A

Abstract: Levansucrase (EC 2.4.1.10) catalyzes both levan polymerization and sucrose hydrolysis. Levan production by recombinant Bacillus subtilis levansucrase SacB‐T305A was investigated. The maximum conversion yield (33.09%) of sucrose to levan and levan yield (115.8 g L–1) were obtained as 30% (wt/vol) and 40% (wt/vol) initial sucrose, respectively. Under highly acidic conditions (pH 3.5 and below), the polymerization not only shifted distinctly to high molecular weight levan but also enlarged the size of low molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The numerical values of BL are summarized in Table 3, indicating that BL biosynthesized using S. salivarius K12 had an M w 500 times larger than BL obtained by L. mesenteroides DSM 20343, whose values corresponded to 15.435 × 10 4 and 26.6 kDa, respectively. The obtained data reveal that BL produced by L. mesenteroides DSM 20343 is classified as a low-molecular-weight polymer, according to Hou et al [69]. However, this is the first report demonstrating the ability of S. salivarius K12 to produce BL over 15 million Da under standardized processing and operational conditions.…”
Section: Characterization Of Bacterial Levan Biosynthesized By Strept...mentioning
confidence: 75%
“…The numerical values of BL are summarized in Table 3, indicating that BL biosynthesized using S. salivarius K12 had an M w 500 times larger than BL obtained by L. mesenteroides DSM 20343, whose values corresponded to 15.435 × 10 4 and 26.6 kDa, respectively. The obtained data reveal that BL produced by L. mesenteroides DSM 20343 is classified as a low-molecular-weight polymer, according to Hou et al [69]. However, this is the first report demonstrating the ability of S. salivarius K12 to produce BL over 15 million Da under standardized processing and operational conditions.…”
Section: Characterization Of Bacterial Levan Biosynthesized By Strept...mentioning
confidence: 75%
“…Because levan is formed by assembling fructose units produced by the hydrolysis of sucrose into glucose and fructose. Many authors (Gonzalez‑Garcinuno et al 45 , Hou et al 46 considered sucrose concentration as one of the factors controlling not only the production of levan but also its molecular weight. Levan production using sugarcane bagasse is very precious, as it helps recycle this waste into a valuable product.…”
Section: Resultsmentioning
confidence: 99%
“…Taleb et al [ 36 ] also reported significantly different results and stated that levan production increased progressively as the pH values rose from 5.5 to 6.5, peaking at the initial pH of 6.5. Levan yield was shown by Hou et al [ 37 ] to be stable between pH 4 and 7.5, with Bacillus subtilis being used to provide the highest yield at pH 6.5. Fermentation was carried out at different temperatures ranging from 20 to 50 °C to study the influence of incubation temperature on levan biosynthesis.…”
Section: Discussionmentioning
confidence: 99%